An Information Support System for Indentifying Farming System Part II : A Case Study of Sleman Regency, Yogyakarta Province - Lilik Sutiarso (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
The second part of the study is to validate the developed information system in a selected farming area. For the primary data, a farm survey is conducted in Sleman Regency, Yogyakarta Province. The sixty (60) household farms in 6 (six) districts are investigated which were grouped into animal-based and tractor-based farms. Based on the farms survey, the results described that the total annual water surplus in the study area is 792 mm that reached from November to April and water deficit is 355 mm from May to October. There is also surplus situation of number of animal-drawn and local equipment for land preparation in each district, but defieciency in number of power tiller and it's matching tillage equipment. The sensitivity analysis indicated those yield and crop proce are the most significant factor in determining the net return of the crop production system.